(untitled) (FUDMA JOURNAL OF SCIENCES, 2021)
Acacia belongs to the family fabaceae among the largest legume genera consisting of eighteen species with the majority of the species distributed in tropical and sub-tropical Africa. Classification of Acacia have remained a daunting task due to it wide spread and also hampered by is large number of species ,prevalence of morphological convergence. Morphological variations in foliar, thorn, inflorescence of some Acacia species found in Zaria for their taxonomic identification at species level were evaluated were Seven species and one variety of Acacia were taxonomically classified using morphological characters. In almost the species leaves were compound bipinnate, alternate and pinnulesare oblong. However the pinnules of A. senegal are obovate. In A. auriculiformis the leaves are simple and sickle-like in shape. Leaves texture ranges from glabrous to pubescent and leaf margin were entire in all the species. The morphological measurement parameters were analyzed using ANOVA cooperation and the results indicate variations among the species. The variations observed in some of the characters could be of taxonomic importance in the identification of the species. Overall ranking indicated that Acacia sieberiana var sieberiana and Acacia sieberiana var villosa were the best with high values of morphological characters of pinna length (3.50±0.11 cm and 3.82±0.16 cm respectively) and number of pinna (18.80±1.32 and 41.70±1.52 respectively). The high values of pinna could be used in solving taxonomic problems associated with Acacia species and in mapping out breeding strategies for the production of cultivars with better foliar yield of Acacia species in Nigeria